Penerapan Teknik Bibliotherapy Untuk Meningkatkan Kepuasan Hidup Siswa Korban Bully Verbal di Sekolah - Durrotunnisa Durrotunnisa; Azam Arifyadi; Munifah Munifah (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of service activities is to increase low life satisfaction in bullied students. Life satisfaction is indicated by the high evaluation of the individual's negative feelings, and cognitive evaluations, including evaluations made by students who are bullied victims. The application of bibliotherapy is carried out as an action in increasing their life satisfaction, so it is hoped that through cognitive evaluation after treatment, they will experience changes that lead to the evaluation of positive feelings related to their lives and their environment. The method used is PTBK which has been carried out with an initial assessment as part of the pre-action in the therapy session. The series of activities carried out is an introduction, followed by core activities where students are directed to read short stories taken from a collection of novels on bullying themes for 3 meeting sessions, then reflection and evaluation are carried out. The results show that there is a difference in the mean scores before and after the action is given. The descriptive analysis conducted showed that there were differences in the pre-test scores (M= 9.0, SD= 2.64) and the post-test scores (M= 16.6, SD= 1.14). The results of the different test showed that there was a significant difference between the pre-test and post-test scores of the bibliotherapy training participants (p < 0.05) of 7.6. It was concluded that students experienced an increase in the ability to conduct cognitive evaluations and reduce the negative feelings they had.